'A dance for all the outcasts': Class and Postcolonialism in Brendan Behan's An Giall and The Hostage. Issue 1 (May 2014) - Pierse, Michael
<x xml:space="preserve">Abstract</x> As Susan Bassnett and Harish Trivedi argue, 'translation does not happen in a vacuum, but in a continuum; it is not an isolated act, it is part of an ongoing process of intercultural transfer'. In understanding Brendan Behan's most celebrated and controversial translation, of his spare Irish language play An Giall (1958) to its riotous English counterpart The Hostage (1958), understanding the problematic 'intercultural transfer' between British and Irish life in the 1950s is crucial. Comparisons between both works reveal significant changes that illuminate Behan's relationship with both nations and provide a sometimes oblique metacommentary regarding his most pressing political and personal anxieties. Yet for all their differences, the plays also share a common desire to transcend the divisions forged by the colonial experience through critical understandings of life on either side of the Irish Sea. In this essay, I argue that Behan's act of transculturation reveals a great deal more reflexivity and depth than many of his critics would allow, developing an iconoclastic dialogue between British and Irish mid-century life.